Towards a Systematic Approach for Capturing Knowledge-Intensive Business Processes - Trier, Matthias; Müller, Claudia (Practical Aspects of Knowledge Management)

Analyzing the Dynamics of Community Formation Using Brokering Activities - Trier, Matthias; Bobrik, Annette (Communities and Technologies 2007)

Hochschulforscher oder Hochschullehrer? Eine Panel-Daten-Analyse wirtschaftswissenschaftlicher Bachelor- und Masterkurse - Lück, Sonja (Hochschulmanagement)

Einheitlicher europäischer Bankenmarkt? Eine Einschätzung der Wettbewerbssituation vor und nach der Finanzkrise - Paul, Stephan; Uhde, André (Wirtschaftsdienst)
Die schwerste Finanz- und Wirtschaftskrise nach dem Zweiten Weltkrieg befindet sich nun schon in ihrem dritten Jahr und wird in weiten Teilen der Öffentlichkeit als Paradebeispiel für ein gravierendes Marktversagen eingestuft. Dies hat über die unmittelbaren staatlichen Rettungsmaßnahmen hinaus den Ruf nach "Mehr Staat in der Kreditwirtschaft!" verstärkt und vielfältige Vorschläge zur Ausweitung und Verschärfung der Beaufsichtigung der Banken hervorgerufen (zuletzt im September 2009 beim Finanzgipfel in Pittsburgh). Noch lässt sich nicht präzise genug abschätzen, welche staatlichen Hilfen für die Kreditwirtschaft erforderlich sein werden und welche Veränderungen in der Bankenregulierung noch vorgenommen werden müssen. Dennoch wird in diesem Beitrag der Versuch einer Skizze möglicher Auswirkungen auf die Wettbewerbssituation des europäischen und deutschen Bankenmarktes speziell im Retail-Segment unternommen. Um die durch die Finanzkrise hervorgerufenen Veränderungen einschätzen zu können, ist jedoch zunächst ein kurzer Blick auf die wichtigsten Etappen und Ergebnisse der europäischen Finanzmarktintegration erforderlich.
Keywords: Finanz- und Wirtschaftskrise; Bankenmarkt

Securitization and systematic risk in European banking: Empirical evidence - Uhde, André; Michalak, Tobias C. (Journal of Banking & Finance)
Using a unique dataset of 592 cash and synthetic securitizations issued by 54 banks from the EU-15 plus Switzerland over the period from 1997 to 2007 this paper provides empirical evidence that credit risk securitization has a positive impact on the increase of European banks’ systematic risk. Baseline results hold when comparing estimated beta coefficients with a control group of similar non-securitizing banks. Building several sub-samples we additionally find that (a) the increase in systematic risk is more relevant for larger banks that repeatedly engage in securitization, (b) securitization is more important for small and medium financial institutions, (c) banks have a higher incentive to retain the larger part of credit risk as a quality signal at the beginning of the securitization business in Europe, and (d) the overall risk-shifting effect due to securitization is more distinct when the pre-event systematic risk is low.
Keywords: Credit risk transfer; Securitization; Systematic risk; Event study

Besteuerung multinationaler Unternehmen in der EU – eine vergleichende Analyse ausgewählter Reformvorschläge - Sureth-Sloane, Caren; Bäumer, Michaela (Zeitschrift für Betriebswirtschaft)

Capitalized investments with entry and exit options and paradoxical tax effects - Schneider, Georg; Sureth-Sloane, Caren (Review of Managerial Science)

Wie attraktiv sind Beteiligungsinvestitionen nach der Begrenzung der Verlustnutzung bei Anteilskäufen durch § 8c KStG? - Sureth-Sloane, Caren; Vollert, Pia (Corporate Finance biz)

The Impact of Tax Optimized Investment Projects on the Effective Group Tax Rate - Müller, Jens; Sureth-Sloane, Caren (Die Betriebswirtschaft)

Industrial services, product innovations, and firm profitability: A longitudinal analysis - Eggert, A.; Hogreve, J.; Ulaga, W.; Münkhoff, Eva (Frontiers Pre-Conference on Service and Solution Innovation, Karlstad)

Exploring the effects of referral reward programs on satisfied and dissatisfied customers - Garnefeld, I.; Münkhoff, Eva; Hogreve, J.; Eggert, A. (2010 AMA Winter Academic Conference, New Orleans, LA)

Disentangling the revenue and cost implications of the service transition: A latent growth analysis - Eggert, A.; Hogreve, J.; Ulaga, W.; Münkhoff, Eva (ISBM 2010 Academic Conference, Boston, MA)

Referral reward programs: A means for service recovery? - Münkhoff, Eva; Garnefeld, I.; Hogreve, J.; Eggert, A. (18th International Colloquium on Relationship Marketing (ICRM), Reading)

Legitimacy of Control - Schnedler, Wendelin; Vadovic, Radovan (Journal of Economics and Management Strategy)

Grenzüberschreitende Verlustverrechnungssysteme in Europa – Vorbilder für eine Reform der deutschen Organschaft? - Sureth-Sloane, Caren; Mehrmann, Annika; Dahle, Claudia (Steuer und Wirtschaft)

Monotonicity and Nash implementation in matching markets with contracts - Haake, Claus-Jochen; Klaus, Bettina (Economic Theory)

DIVIDING BY DEMANDING: OBJECT DIVISION THROUGH MARKET PROCEDURES - Haake, Claus-Jochen (International Game Theory Review)
We discuss a model, in which two agents may distribute finitely many objects among themselves. The conflict is resolved by means of a market procedure. Depending on the specifications, this procedure serves to achieve bargaining solutions such as the discrete Raiffa solution, the Kalai-Smorodinsky solution and the Perles-Maschler solution. The latter is axiomatized using the superadditivity axiom, which in the present context is readily interpreted as resolving a specific source of conflict potential.

Editorial Preface - Kundisch, Dennis

Standortwahl als Entscheidungsproblem des Logistikcontrollings - Betz, Stefan (Der Betriebswirt)

Optimale Darlehensbündel in der privaten Immobilienfinanzierung - Dzienziol, J.; Kundisch, Dennis (Kredit und Kapital)

Zur Preissetzung verschiedener Emittenten bei Indexzertifikaten auf den DAX - Kundisch, Dennis; Klein, C. (Zeitschrift für Bankrecht und Bankwirtschaft)

Der Tracking Error von indexnachbildenden Instrumenten auf den DAX - eine empirische Analyse des ETFs DAX EX sowie zehn Indexzertifikaten - Kundisch, Dennis; Klein, C. (Der Betrieb)

Productivity management for customer solutions --- Towards a performance management system for efficient service value networks - Becker, Jörg; Beverungen, Daniel; Blinn, Nadine; Knackstedt, Ralf; Nüttgens, Markus; Thomas, Oliver; Fellmann, Michael (29th International RESER Conference)

Configurative Service Engineering --- A Rule-Based Configuration Approach for Versatile Service Processes in Corrective Maintenance - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Matzner, Martin (Proceedings of the 42th Hawaii International Conference on System Sciences)

A Framework for Design Research in the Service Science Discipline - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Matzner, Martin; Müller, Oliver; Pöppelbuß, Jens (Americas Conference on Information Systems)

Design Requirements to Support Information Flows for Providing Customer Solutions: A Case Study in the Mechanical Engineering Sector - Becker, Jörg; Beverungen, Daniel; Matzner, Martin; Müller, Oliver (Proceedings of the First International Symposium on Services Science (ISSS'09))

Model-Based Decision Support for the Customer-Specific Configuration of Value Bundles - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Müller, Oliver (Enterprise Modelling and Information Systems Architectures)

Mikroanalytische Begleitung der Steuerpolitik am Beispiel der Erbschaftsteuerreform - Maiterth, Ralf; Houben, Henriette; Broekelschen, Wiebke; Müller, Jens; Sureth-Sloane, Caren (Statistik und Wissenschaft)
Erbschaftsteuer | Inheritance tax | Steuerreform | Tax reform | Steuerwirkung | Tax effects | Steuereinnahmen | Tax revenue | Mikrodaten | Microdata | Simulation | Deutschland | Germany
Keywords: Erbschaftsteuer | Inheritance tax | Steuerreform | Tax reform | Steuerwirkung | Tax effects | Steuereinnahmen | Tax revenue | Mikrodaten | Microdata | Simulation

Linkages between Financial Deepening, Trade Openness and Economic Development: Causality Evidence from Sub-Saharan Africa - Gries, Thomas; Kraft, Manfred; Meierrieks, Daniel (World Development)

The Optimal Distance to Port for Exporting Firms - Gries, Thomas; Naudé, Wim (Journal of Regional Science)

Explaining Regional Export Performance in a Developing Country: The Role of Geography and Relative Factor Endowments - Gries, Thomas; Naudé, Wim (Regional Studies)

Entrepreneurship and regional economic growth: towards a general theory of start-ups - Gries, Thomas; Naudé, Wim (Innovation: The European Journal of Social Science Research)

IT Productivity and Aggregation using Income Accounting - Kundisch, Dennis; Mittal, N.; Nault, B. (10th Workshop on Information Systems and Economics (WISE))

Enhancing the Quality of Financial Advice with Web 2.0 - An Approach considering Social Capital in the private Asset Allocation - Kundisch, Dennis; Zorzi, R. (Proceedings of the 15th Amercas Conference on Information Systems (AMCIS))

An Evaluation Framework for Tracker Certificates during the Financial Crisis and beyond - Kundisch, Dennis; Klein, C. (International Federation of Classification Societies 2009 Conference)

Technical Analysis as a Method of Risk Management - Dorfleitner, G.; Klein, C.; Kundisch, Dennis (Monetary Growth: Trends, Impacts and Policies)

Proceedings of the 4th International Workshop on Enterprise Applications and Services in the Finance Industry

Who Owns the Customer? Disentangling Customer Loyalty in Indirect Distribution Channels - Eggert, A; Henseler, J; Hollmann, S (Proceedings of the 17th International Colloquium in Relationship Marketing)

Can Successful Customer Acquisition Hurt the Existing Customer Base? - Woisetschläger, D; Garnefeld, I; Eggert, A (Proceedings of the 2009 AMA Summer Marketing Educators' Conference)

Referral reward programs: New customer acquisition by opportunism? - Garnefeld, I; Münkhoff, E; Hogreve, J; Eggert, A (Proceedings of the 15th Academy of Marketing Science (AMS) World Marketing Congress)

Musing on a Decade of Customer Value Research in Business Relationships: Where Do We Come From? Where Should We Go? - Eggert, A; Ulaga, W (Proceedings of the 4th International Conference on Business Market Management)

Customer Referral Programs and Customer Retention – Do Rewards Undermine the Retention Effect? - Garnefeld, I; Helm, S; Tax, S; Eggert, A (Proceedings of the 2009 AMA Winter Educators' Proceedings)

Unintended effects of referral reward programs: Exploring the impact of rewards on opportunistic behavior - Garnefeld, I; Münkhoff, E; Hogreve, J; Eggert, A (Proceedings of the 38th European Marketing Academy (EMAC) Conference)

Who Owns the Customer? Exploring Customer Loyalty in a Channel Context - Eggert, A; Henseler, J; Hollmann, S (Proceedings of the 38th European Marketing Academy (EMAC) Conference)

Acceptance of Remote Services – Perception, Adoption, and Continued Usage in Organizational Settings - Wünderlich, Nancy
The increasing employment of information and communication technologies in companies and households has led to considerable changes in the way services are conceived, developed, and delivered. Nancy V. Wünderlich employs a multi-method approach comprising an international qualitative study in Germany, USA and China and a longitudinal quantitative study to analyze remote services. She develops the Interactive Technology-Mediated Service Model (ITSUM) to provide a comprehensive approach of explaining both initial acceptance and repeated, continued usage of remote services in organizations. Finally, she derives managerial implications for remote service providers on how to increase remote service acceptance among their customers and facilitate the export of remote services.

Vorteil Interim Management - Kabst, Rüdiger; Thost, W; Isidor, R

Was zeichnet den erfolgreichen Interim Manager aus? - Kabst, Rüdiger; Isidor, R; Thost, W; Linné, H

Manager auf Zeit: Ignoriert oder akzeptiert? - Kabst, Rüdiger; Isidor, R; Thost, W; Nagel, R

International Fachkräfte gewinnen - Kabst, Rüdiger; Salow, S; Baum, M

Editorial: Motivieren trotz Krise - Kabst, Rüdiger